Cellular senescence promotes endothelial activation through epigenetic alteration, and consequently accelerates atherosclerosis - Sakiko Honda (Nature Portfolio, 2021)
Abstract Senescent vascular cells are detected in atherosclerotic lesion, and its involvement in the development of atherosclerosis has been revealed; however, whether and the mechanism by which endothelial cell (EC) senescence is causally implicated in atherosclerosis remains unclear. We here investigate a role of EC senescence in atherosclerosis by utilizing EC-specific progeroid mice that overexpress the dominant negative form of telomeric repeat-binding factor 2 under the control of the Tie2 or vascular endothelial cadherin promoter. EC-specific progeria accelerated atherosclerosis in mice with target deletion of ApoE. Mechanistically, senescent ECs were markedly sensitive for inflammation-mediated VCAM-1 induction, leading to enhanced monocyte adhesion. Inhibition of NF-κB signaling abolished the enhanced inflammatory responses in senescent ECs, while NF-κB nuclear translocation in response to TNF-α were similar between young and senescent ECs. We found a higher association of VCAM-1 gene with active histone H3 trimethylated on lysine 4, leading to increased NF-κB accessibility in senescent ECs. Our data revealed that EC cellular senescence causes endothelial hyper-inflammability through epigenetic alteration, which consequently accelerates atherosclerosis. Therefore, EC senescence is a promising therapeutic target for the prevention and/or treatment of atherosclerotic disease in elderly population.